Association of Direct Oral Anticoagulants vs. Vitamin K Antagonists With Fractures in Atrial Fibrillation Patients: A Systematic Review and Meta-Analysis - Wu, Xiaojuan; Hu, Linyan; Liu, Jinjin; Gu, Qiuping (Frontiers in Cardiovascular Medicine, 2021)
Background: Current evidence regarding the application of direct oral anticoagulants (DOACs) versus vitamin K antagonists (VKAs) on the fracture risk is inconsistent. Therefore, we conducted a meta-analysis to evaluate the fracture risk of DOACs versus VKAs in patients with atrial fibrillation (AF). Methods: The PubMed and Embase databases were systematically searched until June 2021 for all the studies that reported oral anticoagulants in AF patients. The random-effect model with an inverse variance method was selected to pool the risk ratios (RRs) and 95% confidence intervals (CIs). Results: A total of 10 studies were included in this meta-analysis. Among AF patients receiving anticoagulants, DOAC users showed a reduced risk of any fracture compared to those with VKAs (RR=0.80; 95%CI: 0.70-0.91) regardless of gender (males [RR=0.79; 95%CI: 0.67-0.92] and females [RR=0.71; 95%CI: 0.57-0.89]). Apixaban (RR=0.75; 95%CI: 0.60-0.92) and rivaroxaban (RR=0.73; 95%CI: 0.61-0.88), but not dabigatran and edoxaban, were associated with a decreased risk of any fracture compared with VKAs. DOAC users had decreased risks of osteoporotic fractures (RR=0.63; 95%CI: 0.47-0.84) and hip/pelvic fractures (RR=0.88; 95%CI: 0.79-0.97) compared to those treated with VKAs. Conclusions: Our meta-analysis suggested that the use of DOACs was associated with a reduced risk of any fracture compared with VKAs. Further studies should confirm our findings.